Digital Innovation in Sustainable Mangrove Agroedutourism: Community Empowerment in Patuguran Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
A community service program in Patuguran Village, Rejoso District, Pasuruan Regency, was implemented to address the declining appeal of mangrove tourism due to the COVID-19 pandemic, limited educational facilities, weak digital promotion, and the absence of a sustainability reporting system. The solutions offered include the development of MANGROVEX as a digital agroedutourism platform, the EKOMANG system for standards-based sustainability reporting, and the optimization of social media-based tourism promotion. The implementation of these initiatives has enhanced digital information accessibility, encouraged greater participation from academics and educational tourists, increased engagement through social media and positive visitor feedback, and strengthened the professionalism of Pokdarwis in preparing sustainability reports. This program has made a tangible contribution to revitalizing the attractiveness of Patuguran Mangrove Tourism, improving Pokdarwis management, and supporting sustainable development through the pillars of the blue economy in line with the agendas of SDG 8, SDG 9, and SDG 13.